Union of the Comoros : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative- Decision Point Document. (IMF Staff Country Reports; Country Report ;, 2010)
The assessment shows that despite challenging circumstances, Comoros has made progress on political and economic reforms under IMF-supported programs. Comorian authorities implemented a program for maintaining macroeconomic stability, reducing poverty, improving public financial management, public expenditure policy, and external debt management. The IMF and IDA authorities assessed that, on this decision point, the full delivery of Heavily Indebted Poor Countries (HIPC) and Multilateral Debt Relief Initiative (MDRI) debt relief and sound debt management debt relief will enable the government to better implement the economic reforms that are needed to support sustainable growth in Comoros.